Effect of Thiourea on Growth and Yield of Foxtail Millet - Intodia, S K; Tomar, O P (Annals of Arid Zone, 2016)
In foxtail millet (Setaria iralica (L.) Beauv.) seed-soaking witth thiourea (500 and 1000 ppm) significantly increased growth and grain yield. Foliar sprays of mercaptoethanol and thiourea increased grain yield by 26.9 and 33.7 per cent, respectively, over control. Significant improvement in halVest index was noted with these two chemicals, but straw and biological yields remained unaltered. Since, foliar spray of urea (1000 ppm) did not have any effect, the effects of thiourea are largely attributed to a function of sulphydryl group.